5-Aminosalicylic Acid as a Spectrophotometric Reagent for The Determination of The Drug Terbutaline Sulfate - Mustafa Abusniena, Ashraf; Salhin Mohamed, Abdussalam; Ali Mohmed, Moftah; Jumah Elmagirbi, Antesar (Al-Kimia, 2025)
A new, simple, and highly sensitive spectrophotometric method for determining terbutaline sulfate using 5-aminosalicylic acid (5-ASA) as a reagent has been developed. This method is based on the coupling reaction between the drug and the 5-ASA reagent in a basic medium, resulting in the formation of a blue-colored complex at 25°C, with maximum absorption at 608 nm. The applicability of the method was extensively studied and evaluated based on pH, drug and reagent concentrations, time, and temperature. Beer’s law is valid within the concentration range of 2.0 to 37.3 mg ml-1, demonstrating a correlation coefficient (R²) of 0.9963. The detection limit (LOD) is 0.6 mg ml-1, and the limit of quantitation (LOQ) is 2.0 mg ml-1. The method’s precision and accuracy were evaluated, yielding a relative standard deviation (RSD) of 0.15 for a concentration of 27.0 mg ml-1 and an average recovery of 99.87%. The molar absorptivity was determined to be 1.2 × 104 L mol-1 cm-1, and Sandell’s sensitivity index was measured at 45.8 µg cm2. A 1:2 mole ratio of the complex was established using Job’s method, resulting in a complex formation constant (K) of 8.53 × 105. This method was successfully applied to determine the drug in both pure and pharmaceutical formulations.